QCGN Urges Parliamentarians to Guarantee Future of English-speaking Quebec as Equal Partner in New Official Languages Act - Quebec Community Groups Network (QCGN) (2022)

Brief to the House of Commons Standing Committee on Official Languages on the Topic of Bill C-13, an Act To Amend the Official Languages Act, to Enact the Use of French in Federally Regulated Private Businesses and to Make Related Amendments to Other Acts - O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2022)
The present brief focuses on the first purpose, Bill C-13 amendments to the OLA. This is the topic on which I in my role as research associate at the Quebec English-Speaking Communities Research Network (QUESCREN) have developed the most knowledge.

Modernizing the Official Languages Act : How the Federal Government Got it Wrong with C-13 - Quebec Community Groups Network (QCGN) (2022)

Legislative Brief to House of Commons and Senate Standing Committee(s) on Official Languages : Bill C-13, An Act to amend the Official Languages Act, to Enact the Use of French in Federally Regulated Private Businesses Act and to Make Related Amendments to other Acts (short title: An Act for the Substantive Equality of Canada’s Official Languages) - Task Force on Linguistic Policy (2022)
The TFLP submits that Bill C-13, the proposed modernization of the Official Languages Act (“OLA”), redefines and restructures Canada’s federal Official Languages framework in fundamental and, likely, undesirable ways. It introduces an unprecedented asymmetrical approach to the protection and promotion of Official Languages in Canada and, perhaps even more problematically, to the defence of the linguistic rights and recourses afforded to French speakers and English speakers, both in the Province of Québec, and across the country.

Linguistic Diversity and Use of English and French in Canada : 2021 Census of Population - Quebec Community Groups Network (QCGN) (2022)

Use of French in Federally Regulated Private Businesses Act Abandons English-speaking Quebecers, QCGN Tells Senate Committee - Quebec Community Groups Network (QCGN) (2022)

QCGN Proposes Major Amendments to Federal Bill Modernizing the Official Languages Act - Quebec Community Groups Network (QCGN) (2022)

Brief to House of Commons Standing Committee on Official Languages : Bill C-13, An Act for the Substantive Equality of Canada's Official Languages - Quebec Community Groups Network (QCGN) (2022)
The Official Languages Act is a lifeline for English-speaking Quebec. With Quebec’s Bill 96, the community needs this lifeline more than ever. But with Bill C-13, this lifeline is fraying. Founded in 1995, the Quebec Community Groups Network (“QCGN”) is a not-for-profit organization linking English-language community organizations across Quebec. The QCGN—like the community it serves—is proud to support the protection and promotion of the French language in Canada. The QCGN advocates for linguistic duality in every province and territory. The English-speaking minority in Quebec is a diverse, bilingual, and resilient community that is facing serious economic challenges—in the face of persistent myths and stereotypes. Although the English language itself is not threatened, the English-speaking community’s challenge is in maintaining the community’s vitality and survival in all regions of Quebec.
Keywords: Official Language Minority Community (OLMC)

QCGN Reacts to An Act to Amend the Official Languages Act, to Enact the Use of French in Federally Regulated Private Business Act - Quebec Community Groups Network (QCGN) (2022)

The Tourist Offer of the Whiteley Museum and its Surrounding Area on the Lower North Shore : A Quality Improvement Report - Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2022)
This report analyzes the tourist offer in the eastern part of Quebec’s Lower North Shore, particularly the municipality of Bonne-Espérance, a region where English speakers make up the majority of the population. It focuses specifically on an institution in one of these municipalities, the Whiteley Museum. The report provides the authors’ suggestions to improve tourism development as a means to diversify the economy, potentially help reverse demographic decline, and build community vitality.

Understanding the Long-term Care Experience of Official Language Minorities in Canada: An Environmental Scan - Hsu, Amy T.; Ménard, Alixe; Scott, Mary (2022)
Members of minority and racialized communities across Canada commonly experience disparities in health and healthcare. In the context of the COVID-19 pandemic, minority and racialized individuals have been found to report poorer health outcomes and added barriers to healthcare access. While there is growing understanding of the impact of COVID-19 on individuals who live and work in residential long-term care (LTC) homes and other congregate care settings, little attention has been directed at examining inequities in the care experience and care-related outcomes that equity-seeking groups, including Official Language Minority Communities (OLMC), face within LTC. It’s clear that there is a need for systemic change within LTC; the pandemic, especially in its first two waves, highlighted several pre-existing issues within this sector. To ensure high-quality and equitable care for all aging Canadians, these system-level changes must be informed by evidence.
Keywords: Official Language Minority Community (OLMC)

Not Your Typical Self-Care Seminar : Prioritizing Connection Over Information - Joanisse, Mélanie (2022)

Lunch & Learn : Comprendre l’expérience des soins de longue durée des minorités de langue officielle au Canada: un état des lieux / Understanding the Long-Term Care Experience of Official Language Minorities in Canada : An Environmental Scan - Ménard, Alixe; Scott, Mary; Hsu, Amy (2022)